FLIGHT OPERATIONS MANAGEMENT SYSTEM ADAPTATION TO FUNCTIONING IN INCOMPLETE INFORMATION CONDITIONS - Bondik, Oleksandr (Proceedings of National Aviation University (archive), 2021)
Purpose: The purpose of this article is to present a new approach of Airlines Flight Operations Management System adaptation to functioning in incomplete information conditions. Methods: The article describes two runtime methods which increase the adaptation degree of Airlines Flight Operations Management System to functioning in incomplete information conditions, such as: exception handling and Quality of Service management. Results: The Airlines Flight Operations Management System adaptation overall architecture is given and their components relationships are described. Discussion: The proposed new approach will allow to adapt the Airlines Flight Operations Management Systems’ architecture to functioning in a high degree of uncertainty and incomplete information conditions.